2021
DOI: 10.1038/s41388-021-02022-x
|View full text |Cite
|
Sign up to set email alerts
|

Codon optimality in cancer

Abstract: A key characteristic of cancer cells is their increased proliferative capacity, which requires elevated levels of protein synthesis. The process of protein synthesis involves the translation of codons within the mRNA coding sequence into a string of amino acids to form a polypeptide chain. As most amino acids are encoded by multiple codons, the nucleotide sequence of a coding region can vary dramatically without altering the polypeptide sequence of the encoded protein. Although mutations that do not alter the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 141 publications
0
17
0
Order By: Relevance
“…This codon usage bias has a major role in gene expression, regulating translation speed and protein folding [ 28 , 29 , 30 ], as well as mRNA structure, processing, and stability [ 31 , 32 , 33 , 34 ]. Additionally, in cancer cells, codon usage is optimized to accommodate high translation of cell cycle regulatory genes [ 35 ]. Codon usage bias is species-specific [ 36 ] with biases in arginine usage correlating with speciation [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This codon usage bias has a major role in gene expression, regulating translation speed and protein folding [ 28 , 29 , 30 ], as well as mRNA structure, processing, and stability [ 31 , 32 , 33 , 34 ]. Additionally, in cancer cells, codon usage is optimized to accommodate high translation of cell cycle regulatory genes [ 35 ]. Codon usage bias is species-specific [ 36 ] with biases in arginine usage correlating with speciation [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Purifying selection acting at the amino acid level then reinforces this asymmetry, which can occur in a protein- or tissue-dependent manner. For example, stomach cancers show a pronounced Arg > His bias, whereas skin cancers have a strong Arg > Cys bias [ 35 ]. Determining why such context-dependent behaviors happen, and whether this model of “sequential selection” extends to other signatures, are important next steps for the field.…”
Section: Discussionmentioning
confidence: 99%
“…A recent approach based on experimental data as well as sequence properties of the tRNA genomic loci predicted that at least 314 tRNAs are functional and expressed [34]. Different human cells and tissues show differential regulation of tRNA genes [30,35,36], which include different tRNAs for each proteinogenic amino acid as well as many copies of each tRNA isoacceptor. Even the tRNA isodecoders that share the same anticodon are found in multiple copies.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphic site in AdCIPK12 [A09_ 903,480 (G/K/T) ], located in the predicted first exon region of the gene, A09_903480 (G/K/T) , led no transition (synonymous mutation) in the peanut population. Recent studies proved that synonymous mutations also have dramatic effects on protein output ( Gillen et al, 2021 ). These results indicated that the B09_903480 (G/K/T) sequence polymorphisms might be the actual functional sites.…”
Section: Discussionmentioning
confidence: 99%